Management project performance in Indonesia’s food estate development: A stakeholder, institutional, and communication perspectiv - Nugrahini Susantinah Wisnujati; Amanatuz Zuhriyah; Suwandi S. Sangadji; Suhardi Suhardi (Journal of Project Management)
This study examines the factors influencing the performance of food estate projects in Indonesia, focusing on the roles of leadership, stakeholder engagement, institutional support, and project communication. A positivist research paradigm was adopted, employing a quantitative approach with Structural Equation Modeling (SEM-PLS) to test the hypotheses and analyze the relationships between these variables. The study found that leadership significantly impacts project performance, particularly through its influence on project communication, which serves as a key mediator. While stakeholder engagement did not show a direct significant relationship with project communication, its role in fostering trust, reducing resistance, and ensuring stakeholder needs are met is crucial for overall project success. Institutional support directly contributes to project performance by providing resources, supportive policies, and technical assistance, thereby enhancing the effectiveness of project communication. Project communication, as a mediator, integrates leadership, stakeholder engagement, and institutional support to drive successful project outcomes. These findings underscore the importance of transformational leadership, effective communication, and institutional support in improving food estate project performance in Indonesia. The results offer valuable insights for practitioners and policymakers aiming to enhance project outcomes through strategic management practices.